'I learned to be free': Empowering the self through dance in 2012 Egypt. (1st June 2014) - Khoury, Krystel
In 2012, amid a critical and transitional socio-political situation in Egypt, Bibliotheca Alexandrina started an initiative aiming at developing contemporary dance. The project included the organization of dance workshops for amateurs in various cities of Egypt. Led by eleven local dancers, these workshops consisted of trainings aimed at forming trainers. The methodologies used appeared to have strengthened the awareness of the close relationship between body and mind, revealing new perceptions of the body's potential and awakening a strong feeling of empowerment. By bringing these dynamics to light and examining their implications on the individuals involved in the workshops, the following article aims to open further discussion on how transcultural use of somatic practices can actively participate in enhancing the autonomy of the emergent Egyptian contemporary dance field. It revisits the outcomes of this pioneering project of dance transmission and examines its impact on both dancers and participants.